2017
DOI: 10.1038/s41598-017-02374-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hMASP-2 on the formation of BCG infection-induced granuloma in the lungs of BALB/c mice

Abstract: Tuberculosis, caused by Mycobacterium tuberculosis, affects the functions of the lung and causes high morbidity and mortality rates worldwide. MASP-2 is an executioner enzyme, which plays an essential role in the activation of lectin pathway. In our previous studies, the MASP-2 played a dual role in promoting the progress of lesions in BCG-infected rabbit skin models. However, the really effects of MASP-2 on tuberculosis are unknown. The aim of this study was to investigate the effects of MASP-2 in granuloma f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
(32 reference statements)
1
7
0
Order By: Relevance
“…This result was also supported in two recent animal experiments. Two studies applied human-MASP-2 to mouse and rabbit models, respectively, and found protective effects of MASP-2 on TB infection 31 , 32 . Not only that, it has also been found in humans that mutations in certain sites of the MASP2 gene increase the susceptibility to TB.…”
Section: Discussionmentioning
confidence: 99%
“…This result was also supported in two recent animal experiments. Two studies applied human-MASP-2 to mouse and rabbit models, respectively, and found protective effects of MASP-2 on TB infection 31 , 32 . Not only that, it has also been found in humans that mutations in certain sites of the MASP2 gene increase the susceptibility to TB.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, fresh GC tumor tissues and adjacent normal gastric tissues were collected from patients who underwent surgical resection, blood samples were collected from GC patients diagnosed with primary GC without previously treatment, and paraffin-embedded GC tissues and adjacent noncancerous gastric tissues were obtained from patients who underwent resection between January 2014 and December 2015. Human peripheral blood mononuclear cells (PBMCs) were isolated from fresh blood using Ficoll-Hypaque density gradient centrifugation (Biochrom, Berlin, Germany) according to a previous study [ 16 ]. All of the included patients provided informed consent and signed an agreement.…”
Section: Methodsmentioning
confidence: 99%
“…A brown positive signal was quantitatively expressed as the integrated optical density (IOD), and the average IOD per field for individual lungs was calculated using Image-Pro Plus 6.0 (IPP6) software (Media Cybernetics, Inc., Bethesda, MD, USA). A comparison of the total IODs between each of the two groups was performed [20].…”
Section: Histopathological and Immunohistochemical Examinationmentioning
confidence: 99%